CRITERIA VALUATION OF MANAGEMENT SOLUTIONS FOR INNOVATION AND INVESTMENT DEVELOPMENT OF THE ENTERPRISE UNDER CONDITIONS OF UNCERTAINTY AND CONFLICT (International Journal of Innovative Technologies in Economy, 2020)
In today's complex conditions of enterprise operation, innovation processes in most of them are characterized by a set of complex complex organizational measures, which can be implemented only in the implementation of sequentially parallel information-saturated stages of making various management decisions. The article improves and further develops the criterion evaluation of economic decisions on innovation and investment development of the enterprise under conditions of uncertainty and conflict of production and financial and economic processes while taking into account the peculiarities of investment and innovation processes. Based on research papers, the article improves the classification of decision criteria based on the methods of potential theory and the principles of maximum uncertainty functions and inaccuracy functions, which are related to the values of the estimation functional, characteristics of Bayesian sets and Bayesian surfaces.It is proved that for the formation of criteria for certain aspects of ensuring the appropriate level of innovation and investment development of industrial enterprises in modern economic conditions it is advisable to use decision criteria based on methods of obtaining point estimates of the unknown vector of a priori probability distribution in a set. It is proposed to use the Khomenyuk criterion, as well as the Rosenbluth and Herfindahl-Hirschman indices, which are used in determining the indicators of evaluation of the results of economic activity of mining and processing enterprises of Ukraine. The calculations allowed to determine the company with the most stable level of innovation and investment development during the study period. Based on the research, it is concluded that the results of assessing the level of stability of sustainable innovation and investment development of mining and processing enterprises taking into account the risk obtained using the proposed methodological approach can be used for further development of methodology for criterion evaluation of business decisions and conflict in the course of production and financial and economic processes.